THE SUBCOMMITTEE ON AVIATION HEARING ON LEGISLATION TO LIMIT OR BAN SMOKING ON COMMERCIAL AIRLINERS AGENDA (Tufts Archival Research Center, 2007)
Agenda for the subcommittee on Aviation Hearing on Legislation to ban smoking on Commercial Airliners. Lists panel speakers including James Repace for the “Indoor Air Quality Program” as well as representatives from OSHA, flight attendants and Gray Robertson, president of ACVA Atlantic.